The contribution and challenges faced by private developers in addressing the housing deficit in Ghana - Ebenezer Afrane, 1980- author; Ahmad Ariffian Bujang; Fakulti Geoinformasi dan Harta Tanah (2014)
Thesis (Sarjana Sains (Harta Tanah)) - Universiti Teknologi Malaysia, 2014